INVESTMENT ATTRACTIVENESS OF THE REGIONS OF THE STATE IN THE PRE-WAR PERIOD THROUGH THE PRISM OF FINANCIAL SECURITY - Vakhovych , Iryna; Lakas , Veronica; Servetnyk , Roman (Socio-economic relations in the digital society, 2022)
The article analyzes the investment attractiveness of the regions of the state in the pre-war period through the prism of financial security. A system of indicators for assessing the level of financial security of sustainable development of the region has been formed. According to the proposed methodology, an assessment of the level of financial security of the regions of the state was carried out using the method of comparing actual data with indicators of the level of financial destabilizers (security thresholds). The diagnostics provided for the identification of financial threats and dangers to the sustainable development of individual regions, the level of differentiation of regions according to the state of financial security and the outlining of further directions for improving the mechanisms of regional management. An assessment was carried out on internal indicators of financial security of sustainable development of the region in relation to the regions, characterizing the direct state of financial security of the needs of the economic, social and environmental spheres of the region in comparison with threshold values. The results of the integrated assessment made it possible to position the regions according to the level of financial security of the spheres of sustainable development and confirm the evidence that during the analyzed period the regions of Ukraine were poorly provided with financial resources directed to the sustainable development goals, in particular the environmental and economic components.